A new creep model for studying the non-linear viscoelastic behavior of cooked white, brown and germinated brown Thai jasmine rice by large deformation testing - Panmanas Sirisomboon; Jetsada Posom (My University, 2018)
Abstract
A new creep model with three parameters for non-linear viscoelastic behavior is proposed as εt=ε0(1+tnk1+k2tn), where the applied stress is constant, εt is the strain at retardation time (t), ε0 is the initial strain and k1, k2 and n are constants. The relationship has been proved using data derived from cooked Thai Jasmine rice including white, brown and germinated brown rice samples. The creep test at high strain was conducted on scoops of cooked rice using a compression test rig. The model developed showed very accurate prediction performance with coefficients of determination (R2) between 0.9991–0.9992 and residual standard errors (RSE) between 0.00030–0.0004.
Keywords: Food composition and properties